PROFIL KROMATOGRAFI EKSTRAK ETANOL KELOPAK BUNGA MAMBROS HIJAU - Handayani, Eka Wuri (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Green patchouli or rosella (Hibiscus sabdariffa L.) has many properties and traditionally the flower petals can be used to treat diseases. Based on this, this study aims to identify the chemical content of ethanol extract chromatography from green mrambos flower petals (Hibiscus sabdariffa L.). This research was carried out with the extraction of green mrambos flower petals using maceration method with ethenol 96% solvent. Identification of chemical components was done by tube test and paper chromatography and thin layer chromatography.The results showed that the results of tube test and ethanol extract chromatography from green mrambos flower petals (Hibiscus sabdariffa L.) obtained the presence of flavonoid compounds, polyphenols and saponins which these three compounds could be efficacious as antifungi.Â Â Key word : Ethanol extract of green mambambos flower, tube test, chromatography